An Ethanolic Extract of Ampelopsis Radix Exerts Anti-colorectal Cancer Effects and Potently Inhibits STAT3 Signaling In Vitro - Su, Tao; Bai, Jing-Xuan; Chen, Ying-Jie; Wang, Xin-Ning; Fu, Xiu-Qiong; Li, Ting; Guo, Hui; Zhu, Pei-Li; Wang, Yue; Yu, Zhi-Ling (Frontiers in Pharmacology, 2017)
Colorectal cancer (CRC) is a leading cause of cancer-related morbidity and mortality worldwide. Signal transducer and activator of transcription 3 (STAT3) signaling is constantly activated in CRC, and has been proposed as a pathogenic factor and a therapeutic target of CRC. Ampelopsis Radix (AR), a traditional Chinese medicinal herb, possesses low toxicity and has long been used clinically for the treatment of cancers including CRC. Some constituents of AR have been reported to exert anticancer properties by targeting STAT3. However, the anti-CRC mode and mechanism of action of AR have not been fully elucidated. Here, we investigated the involvement of STAT3 signaling in the anti-CRC effects of AR. Results showed that AR inhibited cell proliferation, induced cell apoptosis, and suppressed cell migration and invasion in human HCT116 and SW480 CRC cells. Mechanistic studies showed that AR potently suppressed STAT3 and Src phosphorylation, and inhibited STAT3 nuclear localization in cultured CRC cells. AR also down-regulated the expression of STAT3 target genes Mcl-1, Bcl-xL and MMP-2 that are involved in cell survival and mobility. Moreover, the cytotoxic effect of AR was diminished by overexpressing STAT3C, a persistent active variant of STAT3. In conclusion, AR exerted anti-CRC effects in vitro and these effects are at least in part attributed to the inhibition of STAT3 signaling. Our findings provide a molecular justification for the traditional use of AR in treating CRC, and a pharmacological basis for developing AR-derived modern anti-CRC agent(s).